2009
DOI: 10.1210/jc.2008-2760
|View full text |Cite
|
Sign up to set email alerts
|

Primary Testicular Dysfunction Is a Major Contributor to Abnormal Pubertal Development in Males with Prader-Willi Syndrome

Abstract: Pubertal development in PWS is characterized by normal adrenarche, variable hypothalamic dysfunction, and hypogonadism due to a unique testicular defect. Primary testicular dysfunction is a major component of hypogonadism in PWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 36 publications
4
62
0
Order By: Relevance
“…Hypogonadotropic hypogonadism was found in more than 25% of the participants in our study, while in males with PWS, severe gonadotropin deficiency is a rare cause of hypogonadism (6,(8)(9)(10). The dissimilarity in hypothalamic-pituitary function between males and females with PWS might be explained by the divergence in the regulation of FSH secretion between normal males and females.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Hypogonadotropic hypogonadism was found in more than 25% of the participants in our study, while in males with PWS, severe gonadotropin deficiency is a rare cause of hypogonadism (6,(8)(9)(10). The dissimilarity in hypothalamic-pituitary function between males and females with PWS might be explained by the divergence in the regulation of FSH secretion between normal males and females.…”
Section: Discussionmentioning
confidence: 47%
“…We found that pubertal development in PWS females, as in males, is characterized by normal adrenarche followed by pubertal arrest. Most females with PWS had variable hypothalamic dysfunction and a unique pattern of ovarian dysfunction characterized by extremely low or undetected inhibin B along with normal AMH levels, resembling the findings of the primary testicular defect in PWS males (10). A small subgroup of women, however, showed detectable inhibin B levels, albeit subnormal for their age, which might be compatible with partial ovarian follicular development.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although the hypogonadism in PWS has long been believed to be entirely hypothalamic, resulting in low gonadotropins and subsequent low gonadal hormones, recent studies have suggested that there is a combination of hypothalamic and primary gonadal deficiencies. [30][31][32] That conclusion was largely based on absence of hypogonadotropism and abnormally low inhibin B in both sexes. In a recent study, all 20 individuals with PWS who were evaluated had brain abnormalities that were not found in 21 sibs or 16 individuals with early-onset morbid obesity who did not have PWS.…”
Section: Other Endocrine Issuesmentioning
confidence: 99%
“…Boys and adolescents present normal/low AMH, low inhibin B, normal/low testosterone and normal/high FSH and LH (43)(44)(45).…”
Section: Primary Hypogonadism With Germ Cell-specific Dysfunctionmentioning
confidence: 99%